Big data analytics: a predictive analysis applied to cybersecurity in a financial organization - Pereira, Pedro Filipe Martins Tourais (2019)
Project Work presented as partial requirement for obtaining the Master’s degree in Information Management, with a specialization in Knowledge Management and Business Intelligence